What were the risk factors and trends in antimicrobial resistance for enteric fever in London 2005‐2012?. Issue 6 (June 2017) - Dave, Jayshree; Warburton, Fiona; Freedman, Joanne; de Pinna, Elizabeth; Grant, Kathie; Sefton, Armine; Crawley‐Boevey, Emma; Godbole, Gauri; Holliman, Richard; Balasegaram, Sooria
Abstract : Purpose. : A study was undertaken to determine the risk factors and trends in antimicrobial resistance for enteric fever. Methodology. : Demographic, antimicrobial susceptibility, typing and epidemiological data were examined for 2005‐2012 in patients with enteric fever in London. Single and multivariable logistic regression was used to determine the risk factors associated with antibiotic resistance. Results. : 453 cases with Salmonella enterica subsp. enterica serovar Paratyphi A, 17 with S . Paratyphi B and 611 with S. enterica subsp. enterica serovar Typhi were examined. For travellers, 335 (88%) of S. Paratyphi A isolates were resistant to ciprofloxacin, but resistance to other antimicrobials was low. Almost 80% (395) of the S . Typhi isolates were resistant to ciprofloxacin, 131 (26%) to ampicillin, 131 (27%) to chloramphenicol, 137 (28%) to trimethoprim and 171 (28%) to sulphonamide. None of the isolates were resistant to cephalosporins. A trend analysis for S . Typhi isolates showed no significant change in resistance to ampicillin, chloramphenicol, sulphonamide and trimethoprim or for multidrug resistance ( P =0.38). Overall resistance to ciprofloxacin increased for S . Paratyphi A ( P =0.018) and for S. Typhi ( P <0.001) but fell for S . Typhi in 2011‐2012. Resistance profiles were reflected by specific phage types and countries visited by the travellers. Conclusions. : The proportion of S . Typhi strains resistant to ampicillin, chloramphenicol and cotrimoxazole remained steady for the period 2005‐2012. There was a significant increase in a trend for resistance to ciprofloxacin which increased until 2010, followed by a fall in 2011‐2012. S. Paratyphi resistance to ciprofloxacin increased until 2012. Specific phage types were associated with resistance to specific antimicrobials and travel abroad.